2012
DOI: 10.1016/s1734-1140(12)70954-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of ABCB1 polymorphism frequency in breast cancer patients from Poland

Abstract: Thus, no significant differences in the studied polymorphism frequencies were observed. It is then suggested that the studied polymorphisms, although probably good candidates in other tissue cancer types, might not be good predictive factors in breast cancer risk or development in Caucasians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
6
11
0
Order By: Relevance
“…These findings are concordant with those in a study by Rubis et al (2012) that involved 209 patients and 202 controls from Poland [cases: GG = 43.5, GT+GA = 44.5 and AA+TT = 12%; controls: GG = 34%, GT+GA = 52.5% and AA+TT = 13.5%]. On the other hand, six studies (2 involving BC patients and 4 involving patients with all cancers) from seventeen studies that evaluated G2677A/T polymorphism that were included in a meta-analysis revealed TT genotypes of G2677A/T to be associated with cancer risk in general (Wang et al, 2013a).…”
Section: Discussionsupporting
confidence: 93%
“…These findings are concordant with those in a study by Rubis et al (2012) that involved 209 patients and 202 controls from Poland [cases: GG = 43.5, GT+GA = 44.5 and AA+TT = 12%; controls: GG = 34%, GT+GA = 52.5% and AA+TT = 13.5%]. On the other hand, six studies (2 involving BC patients and 4 involving patients with all cancers) from seventeen studies that evaluated G2677A/T polymorphism that were included in a meta-analysis revealed TT genotypes of G2677A/T to be associated with cancer risk in general (Wang et al, 2013a).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with a number of previous reports [16, 18, 21, 23, 24], our findings revealed no significant association between this polymorphism and breast cancer development. Otherwise, Gutierrez-Rubio et al [24] did not find differences in the distribution of C3435T polymorphism between breast cancer patients and controls.…”
Section: Discussionsupporting
confidence: 93%
“…This non-synonymous variation is associated with altered P-gp activity. To date there have been vast number of reports correlating the presence of these three SNPs with treatment response and disease predisposition and progression (renal tumor, Chron's disease and ulcerative colitis, Parkinson's disease, schizophrenia, Alzheimer, HIV infection) [9,[17][18][19][20][21]. Most common approach in determination of the influence of gene variation is haplotype assessment because it may provide a better understanding of the observed inconsistences and are promising predictor of the functional consequences of ABCB1 polymorphisms.…”
mentioning
confidence: 99%